2018
DOI: 10.1155/2018/2914036
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a No-Insulation BSCCO Toroidal Magnet Applied in Magnetic Confinement Fusion

Abstract: At present, the Tokamak has become a mainstream form of the magnetic confinement fusion device. The toroidal field (TF) magnet in the Tokamak system is required to generate a high-steady field to confine and shape the high temperature plasma. To secure high current density and high thermal stability, the no-insulation (NI) winding technique is used in the fabrication of the TF magnet. During plasma operation, heat is generated in the TF magnet caused by the interaction with central solenoid (CS) coils, poloida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…e methods of this research include literature research, information research, and empirical analysis, as shown in Figure 2 [15].…”
Section: E Relationship Between Agricultural Products and Agricultura...mentioning
confidence: 99%
“…e methods of this research include literature research, information research, and empirical analysis, as shown in Figure 2 [15].…”
Section: E Relationship Between Agricultural Products and Agricultura...mentioning
confidence: 99%
“…In previous studies [18][19][20], the NI coil's detailed distributed circuit model consists of N t turns, and each turn is divided into Div elements, as shown in figure 1. The total number of elements in the coil is N, which equals N t × Div.…”
Section: Distributed Circuit Modelmentioning
confidence: 99%
“…In order to calculate the magnetic field produced by the coil, the ECG model is coupled to a commercial finite element method (FEM) software, COMSOL Multiphysics, and uses external Matlab subroutines for the current distribution. In [19] the authors built a FEM-circuit model in Ansys to remove the needs of external Matlab codes, and each element per turn of the coil in the FEM model is coupled to the inductors in the circuit model built in the same software. Then, the inductances in the circuit were calculated through the FEM model.…”
Section: Introductionmentioning
confidence: 99%
“…The no-insulation (NI) coil concept has been actively investigated since it was introduced over a decade ago. NI HTS coils have been successfully tested in the high field magnet community for various non-fusion applications [18][19][20][21]. The slow current charging time [18][19][20], however, is a potential issue when the NI coil design concept is applied for operating large scale fusion magnets, particularly for the central solenoid where a fast current ramping is needed for plasma startups [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…NI HTS coils have been successfully tested in the high field magnet community for various non-fusion applications [18][19][20][21]. The slow current charging time [18][19][20], however, is a potential issue when the NI coil design concept is applied for operating large scale fusion magnets, particularly for the central solenoid where a fast current ramping is needed for plasma startups [22,23]. Stellarators and other fusion devices such as a field-reverse configuration (FRC) device, however, do not need a fast ramping field to startup plasma and the NI coils can be promising.…”
Section: Introductionmentioning
confidence: 99%